Modulation Effects of Cordycepin on Voltage-Gated Sodium Channels in Rat Hippocampal CA1 Pyramidal Neurons in the Presence/Absence of Oxygen. (31st October 2017) - Liu, Zhi-Bin; Liu, Chao; Zeng, Bin; Huang, Li-Ping; Yao, Li-Hua
Abstract : Our previous study revealed that cordycepin features important neuroprotective effects against hypoxic insult by improvement of neuronal electrophysiological function. Modulation on voltage-gated sodium channel (VGSC) in CA1 neurons is the initial event during hypoxia/ischemia. However, no study comprehensively investigated cordycepin on VGSC. Hence, this study investigated modulation effects of cordycepin on VGSC not only in oxygen physiological conditions but also in acute oxygen deprivation injury conditions. Results revealed that cordycepin (80  μ M) reduced the amplitude of VGSC currents ( I Na ) (77.6% of control, p < 0.01 ) within 1 min of drug exposure coupled with a negative shift in steady-state inactivation and prolonged recovery time course from inactivation. Additionally, this mild reduction on the peak of I Na induced by the pretreatment with cordycepin can attenuate and delay the following hypoxia causing rapid dramatic decrease in I Na with no additive change in the voltage dependence of inactivation. As modulation on VGSC in CA1 neurons represents the initial event during ischemia, we propose that suppression effect of cordycepin on VGSC is an important neuronal protective mechanism that may enhance neuronal tolerance to acute oxygen deprivation and delay hypoxia-induced neuronal injuries.